UPLIFT AND EXHUMATION HISTORY OF THE PRECAMBRIAN BASEMENT, NORTHERN TARIM: EVIDENCE FROM APATITE FISSION TRACK DATA - Zhu W.B.; Zhang Z.Y.; Shu L.S.; Lu H.F.; Wang S.L.; Yang W.; Su J.B.; Wan J.L. (My University, 2007)
Kuruktag uplift is located to the north of the Tarim basin where the Precambrian crystalline basement rocks are widely crop out. An Archean complex occurs near Qingir village, and is composed of grey gneiss, amphibolite, schist, migmatite and marble. The Neoproterozoic strata occur in Xingdi, Xishankou, Xinger and Saimashan areas in the western Kuruktag, unconformably overlie the Paleoproterozoic to Mesoproterozoic gneisses, amphibolites and schists and are unconformably overlain by the Early Paleozoic rocks. Thus, it is perfect place for understanding the thermal evolution of the Precambrian basement of the Tarim basin. The purpose of this study is to detect that: 1 when were the basement rocks exhumed to the surface initially? 2 did the basement rocks of the Tarim craton experience reburial and re-exhumation? and 3 the history of thermotectonic evolution of the basement rocks respond to the different tectonic events occurred at Tarim continental margins. In order to obtain information about the exhumation history and processes of cooling in the northern Tarim, fission track methods on apatite were used. Ten apatite-bearing samples were collected from two sides of the Xingdi fault in the Kuruktag uplift. Pooled ages range from 146.0 ± 13.4 to 67.6 ± 6.7Ma. Mean track lengths range from 11.79 ± 0.14 to 13.89 ± 0.27 μm. These samples can be divided into three groups depending on their ages and structural position. Group A will refer to samples F2, F3, F4, F5 and F8 with AFT apparent ages about 100-110Ma., generally associated with areas undeformed by the faults. Group B will refer to samples F7, F9 and F10 with AFT apparent ages lower than 80Ma, mostly structurally associated with hanging wall situations close to the faults. Group C will refer to sample F11 which has the oldest apparent age of 146.0 ± 13.4Ma. The thermal history modeled result shows four periods of exhumation in the Kuruktag uplift occurred in late Early Jurassic (180Ma), Late Jurassic-Early Cretaceous (144-118Ma), early Late Cretaceous (94-82Ma) and Late Cenozoic (about 10Ma). These uplift events recorded by the apatite fission track data in the Kuruktag are assumed to be in response to be the result of far-field effects from the multi-stage collisions and accretions of terranes in the south Asian continental margin.
Keywords: EXHUMATION; FISSION TRACK; PRECAMBRIAN BASEMENT; TARIM; THERMAL HISTORY; Archean; Cretaceous; Jurassic; Cambrian; Neoproterozoic; Mesoproterozoic; Paleoproterozoic; Precambrian::Archean; Докембрий::Архей; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская; Paleozoic::Cambrian; Палеозой::Кембрийская; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская